Circular RNAs: Emerging Modulators in the Pathophysiology of Polycystic Ovary Syndrome and their Clinical Implications - Mazloomi, Sahar; Mousavi, Vahide; Aghadavod, Esmat; Mafi, Alireza (Current Molecular Medicine, 2024)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine/metabolic disorder in women of reproductive age. PCOS is characterized by hyperandrogenism, polycystic ovary morphology, and ovulatory dysfunction/anovulation. It involves multiple effects in patients, including granulosa/theca cell hyperplasia, menstrual disturbances, infertility, acne, obesity, insulin resistance, and cardiovascular disorders.Biochemical analyses and the results of RNA sequencing studies in recent years have shown a type of non-coding RNAs as a splicing product known as circular RNAs (circRNAs). Several biological functions have been identified in relation to circRNAs, including a role in miRNA sponge, protein sequestration, increased parental gene expression, and translation leading to polypeptides. These circular molecules are more plentiful and specialized than other types of RNAs. For this reason, they are referred to as potential biomarkers in different diseases. Evidence suggests that circRNAs may have regulatory potentials through different signaling pathways, such as the miRNA network.Probably most experts in the field of obstetricians are not aware of circRNAs as a useful biomarker. Therefore, this review focused on the researches that have been done on the involvement of circRNAs in PCOS and summarized recent supportive evidence, and evaluated the circRNA association and mechanisms involved in PCOS.
Keywords: biomarker